PERBANDINGAN PENGUKURAN LEMAK SUSU SEGAR DAN ULTRA HIGH TEMPERATURE (UHT) DENGAN METODE GERBER DAN ULTRASONIC - Ismiarti Ismiarti; Desti Retno Purwitasari (ANGON: Journal of Animal Science and Technology, 2022)
Background. Fat in milk is one of the important components that can represent the quality of milk. Measurement of standard fat content using the Gerber method while ultrasonic as an alternative. This study aims to determine whether there is a difference between the two methods in fresh and UHT milk samples. Material and methods. Thirty pieces of fresh milk and 18 pieces of UHT milk were tested using the gerber and ultrasonic methods. The data obtained was then tested using the T test between the two methods on the two types of samples. Results. The results obtained for measuring fat content using the Gerber method were higher than ultrasonic (3.63 ± 0.13 vs. 3.44 ± 0.12%) and significantly different (p <0.01). The fresh milk sample produced a linear regression with the equation Y=0.915X+0.1149 and a correlation value of R2=0.946 and R=0.973. Measurement of fat content in UHT milk using this method also showed the same difference (2.97 ± 0.25 vs. 2.71 ± 0.29%; p <0.01). The UHT milk sample produces a regression equation Y=1.021X-0.323 with R2=0.899 with R=0.948. Conclusion. The conclusion drawn is that there are differences in results between measurements of fat content and ultrasonic measurements which are lower than gerber.